The impact of the hybridisation of dactylopius opuntiae cockerell cochineal lineages on the biological control of cactus weeds - Mofokeng, Kedibone (Rhodes University, Faculty of Science, Department of Zoology and Entomology)
In an attempt to control the harmful invasive alien plant, Opuntia megapotamica Arechav. (Cactaceae), a population of the cochineal insect Dactylopius opuntiae Cockerell (Dactylopiidae) (known as the 'engelmannii' lineage) is being considered as a potential biological control agent. This lineage of cochineal and the already established 'ficus' and 'stricta' lineages of the same cochineal species will inevitably hybridise where they occur in sympatry, possibly influencing the efficacy of the lineages on their respective hosts. Laboratory studies were conducted to investigate the likely outcomes of hybridisation between the 'engelmannii' and 'ficus' lineages. Detailed hybridisation trials, during which individual insects were manipulated and crossed, were used to compare the host affinity of Fâ‚ and Fâ‚‚ hybrids between the 'ficus' and 'engelmannii' lineages with the host specificity of the two pure-bred lineages. Host affinity was determined by plotting the net rate of increase (R) of a cochineal population developing on one host plant species against R on the other host plant species. Fâ‚ hybrids were less species-specific than the purebred lineages in both crosses. Thus, the first generation will most likely remain effective in controlling both plant species in the field. Fâ‚‚ hybrids produced a mixture of purebred and hybrid genotypes, with a higher net rate of increase when compared to purebred nymphs on their alternative host. Biological control of both Opuntia ficus-indica (L.) Mill. (Cactaceae) and O. megapotamica in the Eastern Cape Province, where both invasive alien plant species occur together, could be enhanced by the less specific nature of the Fâ‚ progeny, which developed equally well on both O. megapotamica and O. ficus-indica; but this benefit will be reduced by the loss of host specificity of Fâ‚‚ progeny. The success of biological control would depend on whether the species-specific nymph encounters its target host, because the less specific nymphs will have little effect on controlling either weed. These findings indicate that only purebred D. opuntiae lineages should be released in monocultures of their targeted weed. Long-term consequences of hybridisation should be monitored in the field.
Keywords: Dactylopius -- South Africa -- Eastern Cape; Cochineal insect -- South Africa -- Eastern Cape; Opuntia -- South Africa -- Eastern Cape; Dactylopius Hybridization -- South Africa -- Eastern Cape; Insect-plant relationships; Weeds Biological control -- South Africa -- Eastern Cape; Host affinity